ANALISIS PENDAPATAN PETANI TUMPANGSARI DI KESATUAN PEMANGKUAN HUTAN BOJONEGORO - Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1990)
Taungya farming system  has given peasants an opportunity to produce some food  without  getting  involved in forest planting  activities. It is not only  cheap, but also very  attractive to peoples around the  forest. This report was a result of data processing of  peasant's income  in  taungya   farming  system in Bojonegoro Forest District, East Java,   early in 1986.The total peasant's income consists of taungya farming income, other forest  activities  income,  and  income  of  non forest   activities.  Generaly,  the share of each  type  of income    to the average total  peasant's income per year is concecutively 36.8 % (Rp 57,381) of  taungya  farming income;  26.9 % (Rp 41,976) of  other  forest  activities  income  and  36.3.   % (Rp 56,473)  of  non  forest  activities  income.The proportion of  taungya  income to  total  income  of  lnmas peasants (55.8%) is higher  than  Non-Inmas  peasants (21.8%); whereas  peasants working on a low site  quality    have proportion of taungya income to total income, 12.3%, which is lower than those  working  on a  site  with  higher  quality (50.1%).In fact, peasant's income that resultfrom forest activities, especially taungya   farming  still  could  not  cope  withtheir  poverty.   Average   total  income   of  peasants is  Rp  50,814 per capita  in  a year or only 77 % of  the minimum living standard  cost  only.   Nevertheless,  the  average   total  income   of  peasants  had good  distribution,   as far as it is concerned  this would  not  cause an alarming  trouble   to  the  social   community.